MMP-2 siRNA inhibits radiation-enhanced invasiveness in glioma cells. - Aruna Venkata Badiga (Public Library of Science (PLoS), 2011)
Background Our previous work and that of others strongly suggests a relationship between the infiltrative phenotype of gliomas and the expression of MMP-2. Radiation therapy, which represents one of the mainstays of glioma treatment, is known to increase cell invasion by inducing MMP-2. Thus, inhibition of MMP-2 provides a potential means for improving the efficacy of radiotherapy for malignant glioma. Methodology/principal findings We have tested the ability of a plasmid vector-mediated MMP-2 siRNA (p-MMP-2) to modulate ionizing radiation-induced invasive phenotype in the human glioma cell lines U251 and U87. Cells that were transfected with p-MMP-2 with and without radiation showed a marked reduction of MMP-2 compared to controls and pSV-transfected cells. A significant reduction of proliferation, migration, invasion and angiogenesis of cells transfected with p-MMP-2 and in combination with radiation was observed compared to controls. Western blot analysis revealed that radiation-enhanced levels of VEGF, VEGFR-2, pVEGFR-2, p-FAK, and p-p38 were inhibited with p-MMP-2-transfected cells. TUNEL staining showed that radiation did not induce apoptosis in U87 and U251 cells while a significant increase in TUNEL-positive cells was observed when irradiated cells were simultaneously transfected with p-MMP-2 as compared to controls. Intracranial tumor growth was predominantly inhibited in the animals treated with p-MMP-2 alone or in combination with radiation compared to controls. Conclusion/significance MMP-2 inhibition, mediated by p-MMP-2 and in combination with radiation, significantly reduced tumor cell migration, invasion, angiogenesis and tumor growth by modulating several important downstream signaling molecules and directing cells towards apoptosis. Taken together, our results demonstrate the efficacy of p-MMP-2 in inhibiting radiation-enhanced tumor invasion and progression and suggest that it may act as a potent adjuvant for radiotherapy in glioma patients.